Pengaruh Inovasi Produk dan Strategi Pemasaran terhadap Kinerja Usaha Kuliner Kreatif - Alliyah Puteri Selyndra; Fitria Nur Nilamsari; Nadila Maulida Mahmud; Nazwa Amanda Az'zahra; Nandha Narendra Muvano (Shofanah Media Berkah, 2026)
This study examines the influence of product innovation and marketing strategies on the business performance of creative culinary MSMEs. Increasing market competition requires MSME actors to continuously innovate and implement creative marketing strategies to enhance competitiveness and marketing performance. Various quantitative studies indicate that product innovation and marketing strategies have a positive and significant impact on business performance, both partially and simultaneously. Therefore, effective management of product innovation and marketing strategies is a key factor in achieving sustainable performance and competitive advantage for culinary MSMEs.